Characterization of aerogels from chemo-enzymatically oxidized galactomannans as novel polymeric biomaterials. (August 2017) - Rossi, Bianca; Ponzini, Erika; Merlini, Luca; Grandori, Rita; Galante, Yves M.
Graphical abstract: Highlights: Aerogels from laccase/TEMPO-oxidized, lyophilized galactomannans were characterized. We refer to EOLFG, EOLSG and EOLGG for, respectively, fenugreek, sesbania and guar. EOLSG and EOLGG have similar properties. EOLFG gave the most stable aerogel. All three aerogels were characterized by SEM, thermal and X-ray analysis. The oxidative cross-linking does not seems to affect thermal stability. After enzymatic depolymerization, ESI-MS profiles in positive mode were established. Abstract: Aerogels were obtained from laccase/TEMPO-oxidized galactomannans (GM) of the leguminous plants: fenugreek, sesbania and guar, with several potential applications, such as biocompatible, biodegradable "delivery systems" (DS) of active principles. Chemo-enzymatic oxidation of GM in aqueous solution caused a viscosity increase up to fifteen-fold, generating structured, elastic, and stable hydrogels, presumably due to formation of carbonyl groups from primary OH's on the polymers and subsequent establishment of hemiacetalic bonds with available free hydroxyl groups. Upon lyophilization of these hydrogels, water-insoluble aerogels were generated, capable of uptaking an aqueous solution several times their own weight. In the present paper, these aerogels were further characterized by ESI-MS after enzymatic depolymerization, scanning electron microscopy, thermal and X-ray analyses. Fenugreek confirmed to be more structured and stable compared to guar and sesbania aerogels, which is likely due to its higher amount of oxidizable galactose units linked to the mannose backbone (i.e., Gal : Man = 1:1) and, therefore, to more extensive cross-linking of the resulting elastic gel.